(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The text reproduces the speech, accompanied by some references, presented at the Conference "Ten years of anti-mafia code - prevention measures: analysis and prospects", held on 29 September 2021 at the University of Milan. Through a diachronic examination of the living law of the last decade, the author draws an anthropomorphic vision of the Anti-Mafia Code, showing its limits and potential, both on the side of the judicial administration of seized and confiscated assets, and on that of recovery for social purposes.